Linking Transformational Leadership to Employee Performance Through Work Engagement: Study at STIE Mulia Pratama Bekasi - Nurfai Nurfai; Sri Waluya; Hadi Nurhadi (Journal of Marketing Management and Innovative Business Review, 2025)
This study examines the structural relationships among transformational leadership, work engagement, and employee performance within a higher education institution. Drawing upon the Job Demands–Resources (JD-R) framework, the research investigates whether work engagement mediates the effect of transformational leadership on employee performance. A quantitative approach was employed using census sampling, involving 48 permanent employees. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess the measurement and structural models. The results indicate that transformational leadership has a strong and significant positive effect on work engagement. Work engagement, in turn, significantly influences employee performance. However, the direct effect of transformational leadership on employee performance is not statistically significant. Mediation analysis reveals that work engagement fully mediates the relationship between transformational leadership and employee performance. These findings suggest that leadership improves performance primarily by enhancing employees’ psychological engagement rather than through direct performance-driving mechanisms. The study contributes to leadership and organizational behavior literature by highlighting the central role of engagement as a transmission mechanism linking leadership practices to performance outcomes, particularly in the context of higher education institutions. Practically, the findings emphasize the importance of fostering employee engagement as a strategic pathway for improving organizational performance.